2011
DOI: 10.1007/s00423-011-0815-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after conservative and surgical treatment of acute sigmoid diverticulitis

Abstract: Surgical treatment of acute SD is more effective in preventing an eventual relapse of SD than conservative treatment, particularly in patients with recurrent and severe diverticulitis. The necessity for an emergency operation during follow-up is low and did not differ between the two treatment groups. The initial clinical presentation of SD is not a strong predictor of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
1
31
0
2
Order By: Relevance
“…Both conservative and surgical treatment of acute episodes of sigmoid diverticulitis are primarily effective in a large percentage of patients, and mortality in both treatment groups is generally low [ 51 ]. However, the recurrence rates and especially the rehospitalization rates are higher in patients treated conservatively than in those undergoing surgery [ 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both conservative and surgical treatment of acute episodes of sigmoid diverticulitis are primarily effective in a large percentage of patients, and mortality in both treatment groups is generally low [ 51 ]. However, the recurrence rates and especially the rehospitalization rates are higher in patients treated conservatively than in those undergoing surgery [ 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study [19] was identified by cross-referencing. Finally, six articles [19][20][21][22][23][24] were included in the present review.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…From the included studies, five studies were monocentric [19][20][21][22][23] and retrospective observational cohort [19][20][21][22]24] ( Table 1). Overall, 1062 patients were included (518 males and 544 females) with a mean age ranging from 56 to 63 years.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…They also have low rates of subsequent complicated disease or need for emergency surgery (< 6%). [14][15][16][17][18][19] In addition to this, the estimated risk of needing emergency surgery with stoma formation is 1 in 2,000 patientyears of follow-up. 10 Therefore, elective surgery after the initial attack of simple acute diverticulitis is not recommended nor indicated.…”
Section: Indications For Surgical Management Of Diverticular Disease mentioning
confidence: 99%